Rethinking young people's lives through space and place - Sriskandarajah, Anuppiriya (Sociological studies of children and youth, 2020)
How do children and youth create, negotiate, change spaces and places, and assert their rights to space? Taking a socio-spatial approach, this international collection based on empirical research examines how space relates to and informs the social construction of children and youth. Examining the spaces used by children and youth in many different contexts, including neighbourhoods, community centres, schools, public streets, the natural environment, orphanages, early education classrooms, homes, borders, this collection exists at the intersection of the new sociology of childhoods and new materialism. Rethinking Young People's Lives Through Space and Place explores three main themes, how children navigate real and imaginary borders, how space constitutes belonging, meaning-making, and representation, and how space informs learning and identities.